Overexpression of ErbB-1 (EGFR) Protein in Eutopic Endometrium of Infertile Women with Severe Ovarian Endometriosis during the ‘Implantation Window’ of Menstrual Cycle - Jeevitha Poorasamy; Deepali Garg; Juhi Bharti; Aruna Nambirajan; Asmita Patil; Jayasree Sengupta; Debabrata Ghosh (Reproductive Medicine, 2022)
The strong association between endometriosis and infertility is of high clinical significance. High proliferative bias in eutopic endometrium during the secretory phase is a hallmark of endometriosis, which may result in high occurrence of implantation failure and resultant infertility in endometriosis. The ErbB family of proteins regulates the proliferation capacity in the endometrium, potentially causing endometrial hostility to the implantation process in endometriosis. However, our knowledge regarding the involvement of the ErbB family in human endometrium during the window of implantation (WOI) in endometriosis-associated infertility is scant. In the present study, the cellular profiles of immunopositive ErbBs-1 to -4 in the endometrium of endometriosis-free, infertile women (Group 1; n = 11) and in eutopic endometrium of infertile women diagnosed with stage IV ovarian endometriosis (Group 2; n = 13) during the mid-secretory phase were compared using standardized guidelines. Computer-aided standardized combinative analysis of immunoprecipitation in different compartments revealed an overexpression of ErbB-1 in the epithelial, stromal and vascular compartments, along with marginally higher ErbB-3 expression (p < 0.06) in the vascular compartment and ErbB-4 expression (p < 0.05) in the glandular epithelium and stroma in the endometrium during the WOI in women with primary infertility associated with stage IV ovarian endometriosis compared with disease-free endometrium of control infertile women. It appears that changes in ErbBs in the eutopic endometrium during WOI induce anomalous proliferative, inflammatory and angiogenic activities in it, which can antagonize endometrial preparation for embryo implantation in endometriosis. This knowledge appears usable in strategizing methods for the treatment of endometriosis-associated infertility, as well as preempting the oncogenic potential of endometriosis.